Bridging the menopause data gap: a scoping review of status, symptoms, and trends in electronic health records - Robin R. Austin; Malin B. Lalich; Meijia Song; Jeana M. Holt; Carolyn Gibson (Menopause, 2026)
Importance and Objective: Gaps in menopause status classification, reproductive stage documentation, and symptom capture (eg, vasomotor symptoms) within electronic clinical information systems, including electronic health records (EHRs), limit clinical care and menopause research. This scoping review examined how menopause-related data are structured and operationalized within EHR systems and identified gaps in documentation that limit clinical care and research. Methods: We searched Ovid MEDLINE, Scopus, CINAHL, and IEEE Xplore (2004 to March 2026) using terms related to menopause, climacteric, perimenopause, and EHR documentation, supplemented by backward citation searching. Two reviewers independently screened studies, with discrepancies resolved by consensus. Quality appraisal was conducted using the Johns Hopkins Evidence-based Practice framework. Rayyan and Excel facilitated article management, data extraction, and synthesis. Discussion and Conclusion: Nineteen studies met the inclusion criteria. Most were retrospective cohort or cross-sectional analyses conducted in US health systems (2013-2026), with sample sizes from 45 to 307,512 women. Thirteen studies relied on International Classification of Diseases, Ninth and Tenth Revisions (ICD-9/ICD-10) codes to identify menopause-related experiences; however, only nine reported the codes used. Across studies, three interrelated themes emerged: documentation limitations (including the absence of structured reproductive stage fields and reliance on unstructured text), undertreatment of documented symptoms, and underreporting of menopause-related symptoms in the EHR data. Menopause remains inconsistently represented in EHRs, reflecting structural documentation gaps that constrain longitudinal tracking, clinical decision-making, and research reproducibility. Development of standardized menopause common data elements, including structured stage and symptom documentation, will require coordinated, multidisciplinary efforts to improve data quality and support scalable menopause research.